An impedance flow cytometry with integrated dual microneedle for electrical properties characterization of single cell - Mansor, Muhammad Asraf; Ahmad, Mohd Ridzuan; Petrů, Michal; Rahimian Koloor, Seyed Saeid (Artificial cells, nanomedicine, and biotechnology, 2023)
Electrical characteristics of living cells have been proven to reveal important details about their internal structure, charge distribution and composition changes in the cell membrane, as well as the extracellular context. An impedance flow cytometry is a common approach to determine the electrical properties of a cell, having the advantage of label-free and high throughput. However, the current techniques are complex and costly for the fabrication process. For that reason, we introduce an integrated dual microneedle-microchannel for single-cell detection and electrical properties extraction. The dual microneedles utilized a commercially available tungsten needle coated with parylene. When a single cell flows through the parallel-facing electrode configuration of the dual microneedle, the electrical impedance at multiple frequencies is measured. The impedance measurement demonstrated the differential of normal red blood cells (RBCs) with three different sizes of microbeads at low and high frequencies, 100 kHz and 2 MHz, respectively. An electrical equivalent circuit model (ECM) was used to determine the unique membrane capacitance of individual cells. The proposed technique demonstrated that the specific membrane capacitance of an RBC is 9.42 mF/m-2, with the regression coefficients, ρ at 0.9895. As a result, this device may potentially be used in developing countries for low-cost single-cell screening and detection.
Keywords: microfluidic; erytrocyty; Single-cell analysis; analýza jednotlivých buněk; impedance analysis; lidé; Electric Capacitance; buněčná membrána; elektrická impedance; elektrická kapacitance; Electric Impedance; Flow Cytometry; průtoková cytometrie; Single-Cell Analysis; Erythrocytes; impedance flow cytometry; Cell Membrane; Humans